REVIEW : STUDI ETNOBOTANI FARMAKOLOGI DAN FITOKIMIA PANDANUS TECTORIUS DI INDONESIA - Ardi Rustamsyah; Siti Nuraeni; Faizah Min Fadhlillah; Dani Sujana; Mimin Kusmiyati (Jurnal Insan Farmasi Indonesia, 2022)
â€œPandan Lautâ€ (Pandanus tectorius) pandanaceae family, Pandanus odoratissimus is a synonym for P.tectorius. Pandanus fasicularis Lam is also a synonym of P.tectorius , P.odoratissimus. P.tectorius is a shrub that is still not widely used. P.tectorius is also type of plant from the pandan family that grows wild along the coast. P.tectorius is abundant in South Asia, Tropical Australia. This plant in Indonesia grows wild along the northern coast of Java, the Thousand Islands, Sumatra and other Islands. This review aims to provide information on ethnobotany, pharmacological and phytochemical activities of P.tectorius, using the method of literature study from several studies on ethnobotany, pharmacological and phytochemical activities of P.tectoriu, sea pandanus leaves have the potential as a mat sieve material, the fruit has the potential for antioxidant, cytotoxic, antibacterial, analgesic, antihyperlipidemic, antihyperglycemic, antimicrobial and anti- inflammatory activity